2016
DOI: 10.1155/2016/9580485
|View full text |Cite
|
Sign up to set email alerts
|

Coracoid Process Avulsion Fracture at the Coracoclavicular Ligament Attachment Site in an Osteoporotic Patient with Acromioclavicular Joint Dislocation

Abstract: Coracoid fractures are uncommon, mostly occur at the base or neck of the coracoid process (CP), and typically present with ipsilateral acromioclavicular joint (ACJ) dislocation. However, CP avulsion fractures at the coracoclavicular ligament (CCL) attachment with ACJ dislocation have not been previously reported. A 59-year-old woman receiving glucocorticoid treatment fell from bed and complained of pain in her shoulder. Radiographs revealed an ACJ dislocation with a distal clavicle fracture. Three-dimensional … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 13 publications
0
7
0
Order By: Relevance
“…Where there is an avulsion fracture of the coracoid tip, evidence has shown that these injuries can be treated non-operatively. 19…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Where there is an avulsion fracture of the coracoid tip, evidence has shown that these injuries can be treated non-operatively. 19…”
Section: Discussionmentioning
confidence: 99%
“…Where there is an avulsion fracture of the coracoid tip, evidence has shown that these injuries can be treated non-operatively. 19 A case report by Zhang et al 20 describes their management of a patient with a combined coracoid fracture with an ACJ dislocation. This patient underwent fixation using a lateral clavicle hook plate to address the ACJ dislocation and a 3.5 mm cannulated screw for the coracoid fracture.…”
Section: Discussionmentioning
confidence: 99%
“…Avulsion fractures at the angle, 41,51,64,68,73 including the abovementioned horizontal fracture, are functionally classified as type I CF because they destroy the firm scapuloclavicular connection. 51,62,71 Although CF may occur independently, most CF are reportedly associated with neighboring musculoskeletal injuries such as AC dislocation, shoulder dislocation, and J o u r n a l P r e -p r o o f fractures of the acromion, scapular spine, clavicle, and scapular neck.…”
Section: Discussionmentioning
confidence: 99%
“…4 ); 71 we classified this atypical fracture as an avulsion fracture at the angle. Avulsion fractures at the angle, 41 , 51 , 64 , 68 , 73 including the above mentioned horizontal fracture, are functionally classified as type I CF because they destroy the firm scapuloclavicular connection. 51 , 62 , 71
Figure 4 Atypical fracture of the coracoid in a 31-year-old man.
…”
Section: Discussionmentioning
confidence: 99%
“…However, avulsion fracture at the site where the coracoclavicular ligament (CCL) attaches to the coracoid process is very rare; an extensive literature search found only six such cases [3–8]. Four of these cases were adolescents in whom avulsion fracture of the coracoid apophysis attached by the CCL occurred [5–7].…”
Section: Introductionmentioning
confidence: 99%